Keeping Kosher: The Ability of Jewish Soldiers to Keep the Dietary Laws as a Case Study for the Integration of Minorities in the Roman Army - Olshanetsky, Haggai (The Jewish quarterly review, 2023)
The Jewish religion, especially its dietary laws, has been seen as an obstacle to Jewish military service in the armies of the Roman Empire and, thus, is used as a main argument by scholars who deny that Jews served in the Roman army in any considerable numbers. The current essay is the first to examine this claim. Its first part shows that Jews would not have been unique among ethnic army recruits in having dietary restrictions, while the second part presents the diet of the Roman soldier. The third part uses the Jewish soldier as a case study of the capability of any serviceman, no matter his faith or ethnicity, to serve in the army while keeping his customs and traditions with regard to food. Lastly, the article raises the possibility that the Roman logistical system was purposefully structured to ease the service of soldiers from different cultures and ethnicities.